(untitled) - Fiero, Gloria K. (New York, 2006)
Landmarks in Humanities is a single-volume survey of global culture designed for students of humanities, cultural history, and history of the arts. In chronological sequence, Landmarks highlights the most notable monuments of the human imagination--those works of art and architecture, literature, philosophy, and music that have been foremost in shaping the world's cultures.
Keywords: Civilization,Nền văn minh; History,Lịch sử